2020
DOI: 10.29333/aquademia/8444
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Learning as an Instructional Modality in Environmental Science Course during COVID-19

Abstract: The novel coronavirus has forced the closure of schools and universities among countries with COVID-19 cases. Such move has reshaped the contour of education by shifting from face-to-face instruction to full online learning or flexible learning. Among the latter modalities of instruction, flexible learning (FL) appears to be the most practical because it lacks restriction of time, place, and pace of study. This study then aimed to explore the effectiveness of FL as an instructional modality in environmental sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…In a study on flexible learning as an instructional modality during COVID-19, Cortes (2020) found that learners were elated at the prospect of flexible learning. Learners embraced the programme because the learning activities they engaged in provided opportunities for authentic learning, active learning and learner autonomy.…”
Section: The Impact Of Covid-19 In Fostering Equitable Learning Oppormentioning
confidence: 99%
“…In a study on flexible learning as an instructional modality during COVID-19, Cortes (2020) found that learners were elated at the prospect of flexible learning. Learners embraced the programme because the learning activities they engaged in provided opportunities for authentic learning, active learning and learner autonomy.…”
Section: The Impact Of Covid-19 In Fostering Equitable Learning Oppormentioning
confidence: 99%
“…Basically, the implementation of online learning requires the support of electronic devices such as mobile phones, smartphones, laptops, computers, tablets, and Iphones as a means to access information anytime and anywhere (Gikas & Grant, 2013). Online learning is a demand of the 21st century world, especially for the world of education in recent years (Alghasab, 2020;Cortes, 2020;Firdaus et al, 2020;Lockma & Schirm, 2020). Learning that started from face to face turned into a virtual meeting with the term online learning as a result of the COVID-19 pandemic (Rahayu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, it helps teachers establish their identity as researchers, allows them to examine the dynamics of their classrooms, checks on their actions and interactions with students, and validates and challenges their existing practices (Davis, Clayton, & Broome, 2018). Fifth, it improves teaching and learning of particular disciplines, of which one is biological sciences (e.g., Udeani, Atagana, & Esiobu, 2016;Cortes, 2020). Finally, Hine and Lavery (2014) specifically stressed that AR also bridges the gap between theories and practices in science education, enables teacher empowerment, and is an effective form of professional growth and development.…”
Section:  Introductionmentioning
confidence: 99%